Effect of Candesartan on Creatinine and Albuminuria in Geriatric Patients with Diabetic Nephropathy - Luh Gede Sri Yenny; Ni Wayan Rusni (Jurnal EduHealth, 2026)
Diabetic nephropathy (DN) is a major complication of diabetes, leading to proteinuria and declining kidney function. Candesartan, an angiotensin receptor blocker, may offer renal benefits beyond blood pressure control. Its specific effects on creatinine and proteinuria in geriatric DN patients remain underexplored. A cross-sectional study was conducted with 25 geriatric DN outpatients at Puri Raharja Hospital. Using consecutive sampling, subjects receiving 16 mg candesartan daily had their serum creatinine and proteinuria levels evaluated from medical records at baseline and after three months. The cohort (60-82 years) comprised 13 men and 12 women. Initial creatinine ranged from 0.80-2.60 mg/dL, with a final mean of 1.395 ± 0.50 mg/dL. Statistical analysis (paired T-test) showed no significant change in creatinine levels (p=0.892). However, proteinuria significantly decreased post-treatment (Wilcoxon test, p=0.005). Candesartan administration did not significantly reduce serum creatinine in geriatric DN patients over three months. However, the significant reduction in proteinuria indicates a beneficial effect on renal pathology, potentially slowing DN progression in this population.